(untitled) (Journal of Advanced Research in Social Sciences, 2023)
The relation between the sexes has long been founded on the basis of masculine domination. Interpreting biological differences as evidence of male superiority, social institutions - the family, religious and educational institutions as well as the state - have succeeded in grounding this culture in the collective unconscious so that it has come to be viewed as natural. As a result, dominated women internalized this vision and believed in their unworthiness and inability to compete with the dominating male gender. Even the changes in the condition of women brought about by feminist movements obeyed the logic of the traditional sexual division. Such a division, Pierre Bourdieu notes, extends to homosexuals who emulate the relations of domination among heterosexuals. Biological studies, on the other hand, proved that sexual orientations are based on genetic or hormonal differences. The tendency to naturalize the social and socialize the natural has thus created a gender dilemma, reinforcing the binary division of gender and masculine domination. In this context, Alaa Abd al-Hadi’s Nucleo-genre Paradigm (2008), a world poetics paradigm for the study of literary genres, offers a new way of understanding gender that helps resolve the age-old nature-nurture controversy through its distinction between the “Homogeneous Medium” without which gender does not ontologically exist, the “Isomers" or epistemological structural elements that are shared by various genders, and the “Isotopes” or infinite number of aesthetic characteristics that differ from one individual to another. Moreover, it predicts the formation of new gender identities through its notion of the “Arch-isomer,” which results from the union of two different isomers.